Peran Mahasiswa Asistensi Mengajar dalam Adaptasi Teknologi di UPTD SDN Mlajah 2 Kota Bangkalan - Maharena, Viga; Jannah, Ana Naimatul; Koesmini, Astien Diena (Edu Berkah Khatulistiwa, 2024)
Teaching assistance is one of the programs implemented on campus teaching where students who have certain skills help or accompany learning activities at school, one of which is teaching assistance at UPTD SDN Mlajah 2, Bangkalan city. In this program, the student assistants involved have the responsibility to assist in the learning process and enhance students' learning experiences through the use of technology. The main focus is on applied technological innovation, the contribution of student assistance in supporting interactive and interesting teaching. The results of this program show an increase in the quality of learning due to the presence of student teaching assistance and the use of technology. The implications of these findings enable educational institutions to increase the role of student teaching assistants and develop more effective technology-based teaching methods.